Impact of dynamic variability on the operation of CMOS inverter. Issue 19 (1st September 2013) - Ioannidis, E.G.; Haendler, S.; Manceau, J.‐P.; Dimitriadis, C.A.; Ghibaudo, G.
Abstract : The impact of dynamic variability due to low‐frequency fluctuations on the operation of CMOS inverters, which constitute the basic component of SRAM cell, is investigated. The experimental methodology to characterise the effect of dynamic variability in a CMOS inverter is first established based on fast I–V measurements of the load current following the application of a ramp input voltage V in ( t ). It is shown that, for small ramp rise times, the load current characteristics I DD ( V in ) exhibit a huge sweep‐to‐sweep dispersion due to low‐frequency noise. The impact of such dynamic variability sources on the inverter's output characteristics V out ( V in ) is finally demonstrated, revealing a 20% noise margin reduction for the smallest inverter cell.